Design and synthesis of a novel isoleucine-derived Schiff base ligand: Structural characterization, molecular docking, and in vitro biological activity evaluation - Derafa, Wassila; Moustafa, Bassant S.; Mohamed, Gehad G.; Taha, Rania H.; Farhana, Aisha (International Journal of Health Sciences, 2024)
Objective: Schiff bases are versatile chemical compounds extensively used in various applications, including as catalysts, polymer stabilizers, pigments, dyes, and building blocks for organic synthesis. In addition, they exhibit a wide range of biological activities, such as antifungal, antibacterial, antiviral, antiproliferative, antiinflammatory, and antipyretic effects. Methods: A novel Schiff base ligand (HL) was synthesized by condensing isatin with 2,6-diaminopyridine and isoleucine, followed by the preparation of transition metal complexes. The ligand and complexes were characterized using techniques such as elemental analysis, IR, 1H-NMR, UV-vis spectroscopy, mass spectrometry, and thermal analysis. Antimicrobial, antiproliferative activities, and structural investigations through X-ray diffraction and scanning electron microscopy were also evaluated. Results: The complexes were identified as [Cr(L)Cl(H2O)]Cl·2H2O, [Fe(L)Cl2], [M(L)]Cl·nH2O, and [M(L)(H2O)2]Cl, where M represents Mn(II), Cu(II), Cd(II), Co(II), Zn(II), and Ni(II). Thermogravimetric analysis showed initial water loss, followed by decomposition of anionic compounds and ligands. The ligand forms a uninegative-tetradentate bond with the metal ions, and all complexes, except Fe(III), exhibit electrolytic behavior. Most complexes displayed tetrahedral geometry, while Ni(II), Co(II), and Zn(II) had octahedral geometry. The metal complexes showed enhanced antibacterial, antifungal, and antiproliferative activity against MCF-7 breast cancer cells compared to the free ligand. Molecular docking studies indicated inhibitory potential against receptors 1GS4, 2HQ6, 3DJD, and 5JPE. Conclusion: These newly synthesized ligands and complexes show promise as therapeutic agents against infections and cancer, though further studies are needed to understand their mechanisms.